1825 N.H. Laws 74, § 4 - (:unkn) unknown (My University, 1825)
An Act to Regulate the Keeping and Selling, and Transporting of Gunpowder, § 4: Banned transport or carry from town to town, or place to place, any gunpowder for the purpose of peddling or selling by retail.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER